Proceso de Contratación del Personal del Municipio del Cantón Montalvo y la Atención al Usuario - Cisneros Maines, Doris Aracely (2017)
The process of hiring of personnel in the municipality of the canton Montalvo in its beginnings was deficient due to the political pressures of both the councilmen and also by the mayor of the canton, who takes to his personnel of trust with the purpose of having the security of that what is tried in the mayor's office is not manifested in other places, after the passage of the years it has been made clear that the functions must be according to the functional organism established in the Autonomous Municipal Decentralized Governments, in which the details are detailed specific functions they must perform in the performance of their duties and / or duties.